2014
DOI: 10.1002/jor.22617
|View full text |Cite
|
Sign up to set email alerts
|

Disadvantages of interfragmentary shear on fracture healing—mechanical insights through numerical simulation

Abstract: The outcome of secondary fracture healing processes is strongly influenced by interfragmentary motion. Shear movement is assumed to be more disadvantageous than axial movement, however, experimental results are contradictory. Numerical fracture healing models allow simulation of the fracture healing process with variation of single input parameters and under comparable, normalized mechanical conditions. Thus, a comparison of the influence of different loading directions on the healing process is possible. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 44 publications
(96 reference statements)
0
47
0
Order By: Relevance
“…In contrast, when stress is less than optimal, bone resorption dominates [16]. As for comminuted fractures, especially in weight-bearing bone, axial stress easily leads to a transversal shift of bone blocks [17]. Some authors [18] found that intraoperative unstable rotation and poor contact between bone blocks during treatment of femoral nonunion using intramedullary nails was alleviated after bone grafting and insertion of a steel plate to increase local stability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, when stress is less than optimal, bone resorption dominates [16]. As for comminuted fractures, especially in weight-bearing bone, axial stress easily leads to a transversal shift of bone blocks [17]. Some authors [18] found that intraoperative unstable rotation and poor contact between bone blocks during treatment of femoral nonunion using intramedullary nails was alleviated after bone grafting and insertion of a steel plate to increase local stability.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, the axial stress and tension shear stress in the NALCP skeletal model were significantly lower than those in the LCP model. Thus, NALCP enhances the stability of bone blocks under stimulation of a slow walking load and a torsional load [17], improving the fixation effect, preventing lateral displacement of the bone block, and promoting bone healing.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, pure translation and shear torsion does not stimulate callus formation for fracture union. (11)(12)(13)(14) Some authors had suggested that intramedullary nail may not fully eliminate torsion(9,15-19) and distraction at the humerus. (9,19) The rotational stiffness of the nail is largely influence by the nail design and number of interlocking screw placed.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, studies have demonstrated the inhibitory effect of shear forces on wound healing in other collagenous tissues 29,30 . The addition of 2 mm of new, tendon-like tissue over the bursal surface of the supraspinatus tendon has been proposed as a way to reduce the stress within the injured tendon and improve the healing environment for partial-thickness cuff tears 21,22 .…”
Section: Discussionmentioning
confidence: 99%